Enterpreneurhip Modules in Shaping Enterprenerical Character in Elementary Schools - Sofwan, Muhammad; Budiono, Hendra; Khoirunnisa; Pamela, Issaura Sherly; Alirmansyah (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
The current condition of entrepreneurial activities to form entrepreneurial character has yet to be optimally implemented at the elementary school level. This is evident in elementary schools where entrepreneurial activities have not been appropriately programmed, one of which is the absence of an entrepreneurship module. This study aims to develop an entrepreneurship module for forming entrepreneurial character in elementary schools. This research is a research and development. Product development uses the ADDIE model. The subjects of the study were media validators, content validators, language validators, and teachers. The trial subjects were 25 elementary school students. The methods used in collecting data were observation, interviews, and questionnaires. Data collection instruments were questionnaire validation and practicality questionnaires. The techniques used to analyze data were qualitative descriptive analysis and quantitative descriptive analysis. The study results showed that the developed entrepreneurship module had an average validity level of 87.5% with a very valid category and a practicality level of 94.5% with a very practical category. It can be concluded that the entrepreneurship module product in forming entrepreneurial character in elementary schools is feasible to use in the learning process.